Flatwater kayak modelling: a mathematical approach from experimental data - Bueno, D. D.; Romagnoli, C.; Annino, G.; Bonaiuto, V. (VIII Congreso Internacional De Entrenadores De Piragüismo en Aguas Tranquilas, 2022)
Synchronous measurement of applied force and key kinematic variables as linear and angular velocities and accelerations are obtained in flatwater kayaking. The specific equipment needed includes an instrumented paddle, on board sensor and data acquisition system, all of them electronically synchronized at 100Hz frequency [1, 2]. This equipment provides high quality experimental data which are used to feed a recently developed physical a propulsion model for kayaking[3]. By modeling the paddler stroke using mathematical tools and introducing a few physical parameters, mean force, steady average velocity and mass, the model is not only able to approximate the experimental velocity-time curves but also to extract meaningful physical magnitudes that characterize the paddler performance.